Gambaran Tingkat Kecemasan Pada Warga Binaan Perempuan Di Lembaga Permasyarakatan Perempuan Kelas IIA Denpasar - Gusti Ayu Alit Adiari; Ni Luh Putu Suardini Yudhawati (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Anxiety in female residents is a concern experienced by the target citizens during their prison term.The impact of prolonged anxiety leads to mental disorders. Anxiety in female assisted citizens can be experienced by all the target citizens who are in prison, research conducted earlier in 2020 obtained 55.9% of female target citizens experience mild anxiety. This study aims to find out the Picture of Anxiety Level in Women's Assisted Citizens. Methods: This research is cross sectional study. Sampling using purposive sampling technique as many as 115 prisoners in the Women's Penitentiary Class II A Denpasar. This study used an anxiety questionnaire from the Taylor Manifest Anxiety Scale (TMAS). descriptive statistics used in data analysis. Results: Research conducted to 115 inmates at the Class IIA Denpasar Women's Society About anxiety levels classified as mild anxiety as many as 51 respondents (44.3%). Characteristics of respondents namely adult age (26-45) as many as 75 respondents (65,65.3%), based on adult age (26-45) as many as 75 respondents (65,65 2%), based on the case of most narcotics as many as 97 respondents (84.3%), based on the length of time in prison that is 1-4 years as many as 53 respondents (46.1%), based on the last education of most high schools as many as 62 respondents (53, 9%) and marital status were mostly unmarried as many as 43 respondents (37.45%). Conclusion: The level of anxiety of women-assisted citizens in the Class IIA Denpasar Women's Society is mild